2016
DOI: 10.18805/ijar.9646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of poly-herbal mixture and butyric acidon milk production, milk quality and somatic cell counts ofpostpartum Murrah buffaloes

Abstract: This study evaluated the effect of dietary supplementation of poly-herbal mixture and butyric acid on the milk yield, milk quality and somatic cell counts in Murrah buffaloes up to 90 days of lactation. Thirty six Murrah buffaloes were divided into four groups viz.; T0 control (n=9; Body Weight (BW)=666.22±31.30 kg, Most Probable Production Ability (MPPA)=1834 kg, Parity (P)=3.44) without any supplementation, T1 (n=9; BW=661.89±42.13 kg, MPPA=1860 kg, P=3.56) poly-herbal mixture, T2 (n=9; BW=664.22±14.81, MPPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…From the results, it may be deduced that the milk composition (Milk fat, SNF, lactose, milk protein, total solid, FCM, SCM, ECM and GE) has not affected by cumin seed supplementation in dairy cows (Table 2). Present findings were akin to that of Chandra et al (2017) who also observed no significant change in milk protein, lactose and SNF but the values were numerically higher in poly-herbal mixture supplemented groups. Correspondingly, Miri et al (2013) was also found that the cumin seed extract supplementation had no effect on milk fat, protein and lactose percentage in lactating dairy cows.…”
Section: Effect Of Dietary Inclusion Of Cumin Seed On Milk Compositio...supporting
confidence: 72%
See 1 more Smart Citation
“…From the results, it may be deduced that the milk composition (Milk fat, SNF, lactose, milk protein, total solid, FCM, SCM, ECM and GE) has not affected by cumin seed supplementation in dairy cows (Table 2). Present findings were akin to that of Chandra et al (2017) who also observed no significant change in milk protein, lactose and SNF but the values were numerically higher in poly-herbal mixture supplemented groups. Correspondingly, Miri et al (2013) was also found that the cumin seed extract supplementation had no effect on milk fat, protein and lactose percentage in lactating dairy cows.…”
Section: Effect Of Dietary Inclusion Of Cumin Seed On Milk Compositio...supporting
confidence: 72%
“…Current results corroborated well with the findings of other workers (Sharma et al 2014;Singh et al 2019;Kumar et al (2011); Azadi et al (2011) and Preciado et al (2011). In Corroboration, Chandra et al (2017) also observed that the Somatic cell count (SCC) was significantly (P<0.05) lower in poly-herbal mixture and butyric acid supplemented groups as compared to control group in Murrah buffaloes.…”
Section: Effect Of Dietary Cumin Seed Supplementation On Somatic Cell...mentioning
confidence: 87%
“…Chandra et al [47] reported that supplementation with herbal compounds with active substances affect mammary gland secretory cells, with a subsequent increase in milk production and changes in the content of solids-not-fat and protein. Supplementation during all gestation with BCho increased milk production.…”
Section: Discussionmentioning
confidence: 99%
“…The cows supplemented with polyherbal mixture produced more milk than those of without supplementation, and it was significantly (P<0.05) higher in T 1 as compared to control group T 0 . Higher milk production in polyherbal group may be due to galactopoietic activity of some of the herbs like Anethum graveolens, Foeniculum vulgare and Trachy spermumammi (Chandra et al 2017 Table 1 Ingredients of polyherbal mixture and their cost (Rs. )…”
Section: Effect Of Polyherbal Supplements On Milk Yield and Reproductionmentioning
confidence: 99%
“…Singhal (1995) reported that herbal supplementation showed galactopoetic activity and can be considered as an alternative for lactogenic hormones for inducing and enhancing milk yield in crossbred cows. Several researchers have tried various herbal feed supplements like polyherbal galactogogue biscuits (Patel et al 2013) and Asparagus racemosus (Behera et al 2013), poly-herbal mixture (Chandra et al 2017, Chandrasekhar, et al 2019 to improve the productive and reproductive performance, and health status of dairy animals. However, very limited studies have evaluated effects of polyherbal supplements at farmers' field.…”
Section: Introductionmentioning
confidence: 99%